وسائل العلاقات العامة المستخدمة في تحسين صورة المؤسسة جامعة محمد الشريف مساعدية نموذج - بوعديلة شمس الدين; براهمية حسيبة (My University, 2018)
abstract Public relations are of great importance in the modern administrative systems and depend on them for vital roles in highlighting the honorable image of the institution and its services to the public and to establish strong and good relations between them and provide them with the necessary information on the one hand and receive their views and ideas and suggestions on the other hand. As for the effective role played by public relations means to achieve its objectives in institutions, especially university institutions, it serves as a link between the university and its internal and external audiences, as well as the face of the university, which is visible to the outside society through which communication with various institutions and academic bodies Scientific knowledge at all levels and thus convey the image of the university intellectually, culturally and scientifically ---------------------------------- ملخص تحظى العلاقات العامة بأهمية بالغة في النظم الإدارية الحديثة، وتُعتمد عليها لأدوار حيوية في إبراز الصورة المشرفة للمؤسسة وخدماتها للجمهور، وإقامة علاقات وطيدة وجيدة بينهم، وتزويدهم بالمعلومات اللازمة من جهة، وتلقي آرائهم وأفكارهم ومقترحاتهم من جهة أخرى. وللدور الفعال الذي تلعبه العلاقات العامة في تحقيق أهدافها في المؤسسات، وخاصةً الجامعات، دورٌ في ربط الجامعة بجمهورها الداخلي والخارجي، كما تُمثل واجهة الجامعة المرئية للمجتمع الخارجي، ويتم من خلالها التواصل مع مختلف المؤسسات والهيئات الأكاديمية، وإثراء المعرفة العلمية على جميع المستويات، وبالتالي نقل صورة الجامعة فكريًا وثقافيًا وعلميًا.
Keywords: وسائل العلاقات العامة، صورة المؤسسة